Variability of Microbial Particulate ATP Concentrations in Subeuphotic Microbes Due to Underlying Metabolic Strategies in the South Pacific Ocean - Lanpher, Kaycie B.; Popendorf, Kimberly J. (Frontiers in Marine Science, 2021)
Adenosine triphosphate (ATP) is the primary energy storage molecule in metabolic pathways. It is common in marine studies to use particulate ATP (PATP) concentrations as representative of microbial biomass. However, there is growing evidence from culture studies, models, and transcriptional data that PATP concentration varies across microbes and conditions, thus compromising interpretations in environmental settings. Importantly, there is a lack of open ocean studies assessing variations in PATP concentrations and thus a deficiency of information on the key biogeochemical drivers for variability in microbial PATP independent of biomass. In sampling the U.S. GO-SHIP P06E zonal transect (32.5° S) across the eastern South Pacific, from the subtropical gyre to the upwelling waters off Chile, we conducted the first comprehensive transect survey quantifying PATP. PATP concentrations increased toward the upwelling region of the transect, but varied vertically when normalized against three measures of biomass: particulate phosphorus, microbial abundance, and microbial biovolume. Generally, greater biomass-normalized PATP concentrations were observed below the deep chlorophyll maximum. Subdividing the P06E transect into four biogeochemical regimes highlighted distinct metabolic strategies used by microbes. Between these regimes, we found PATP concentrations were representative of biomass in upper surface waters. However, below the deep chlorophyll maximum we observed higher biomass normalized PATP concentrations that we hypothesize were due to less availability of energy sources in those subeuphotic zone waters and abundances of chemoautotrophs in the microbial community. This finding suggests that stored energy was more important for these deeper microbes.